2021
DOI: 10.21037/apm-21-427
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between small intestinal bacterial overgrowth and irritable bowel syndrome and the prognosis of treatment

Abstract: Background:The aim of the present study was to analyze the relationship between small intestinal bacterial overgrowth (SIBO) and irritable bowel syndrome (IBS) and the prognosis of treatment.Methods: A total of127 IBS patients (IBS group) were selected, and based on the results of the methane/ hydrogen breath test, they were divided into SIBO-positive group (subdivided into the antibiotic group, microecological group, and placebo group according to difference in treatment methods) and the SIBOnegative group. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…In the same study, increased IL-1β level was predominantly associated with bloating and loose stools (Bristol type 6). In a recent study, also on patients with IBS, IL-1β levels in the peripheral blood were higher in the SIBO positive group compared to the SIBO negative group [ 21 ]. IL-1β levels decreased significantly after antibiotic treatment strengthening the hypothesis of SIBO’s contribution to elevated IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, increased IL-1β level was predominantly associated with bloating and loose stools (Bristol type 6). In a recent study, also on patients with IBS, IL-1β levels in the peripheral blood were higher in the SIBO positive group compared to the SIBO negative group [ 21 ]. IL-1β levels decreased significantly after antibiotic treatment strengthening the hypothesis of SIBO’s contribution to elevated IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is the most common functional digestive disorder. In developed countries, its prevalence varies between 10% and 15% [56,57]. It is estimated that the incidence of bacterial proliferation of the small intestine in patients with IBS was 51.7% compared to healthy subjects -16.7%.…”
Section: Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%
“…Serum interleukin (IL)-1β levels were higher and serum IL-10 levels were lower in SIBO-positive patients with IBS than in the SIBO-negative group[ 32 ]. Another study also showed that increased IL-1α and IL-1β levels were associated with SIBO[ 33 ].…”
Section: Functional Digestive Diseasesmentioning
confidence: 99%